2000
DOI: 10.1046/j.1365-2656.2000.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent inferiority of first‐time breeders in the kittiwake: the role of heterogeneity among age classes

Abstract: Summary1. Many studies have provided evidence that ®rst-time breeders have a lower survival, a lower probability of success, or of breeding, in the following year. Hypotheses based on reproductive costs have often been proposed to explain this. However, because of the intrinsic relationship between age and experience, the apparent inferiority of ®rst-time breeders at the population level may result from selection, and experience may not in¯uence performance within each individual. In this paper we address the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
176
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(190 citation statements)
references
References 70 publications
13
176
1
Order By: Relevance
“…For example, breeding probability has been shown to be associated with divorce or dispersal in several species [15,24,40]. In addition, in this study population, previous results have provided evidence that the probability of breeding in the following year differs according to previous breeding success (for birds involved in the breeding process) [19,23]. Because of the well-known relationship between breeding success, dispersal and divorce, subsequent breeding probability is likely to vary with any of these covariates, as well as with those associated with breeding success itself [15,16].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…For example, breeding probability has been shown to be associated with divorce or dispersal in several species [15,24,40]. In addition, in this study population, previous results have provided evidence that the probability of breeding in the following year differs according to previous breeding success (for birds involved in the breeding process) [19,23]. Because of the well-known relationship between breeding success, dispersal and divorce, subsequent breeding probability is likely to vary with any of these covariates, as well as with those associated with breeding success itself [15,16].…”
Section: Discussionmentioning
confidence: 56%
“…The classical explanation for this pattern is the trade-off between current and future reproduction [35,36]. Investment in current reproduction may have a cost in terms of reduced survival or future reproduction [4], and experienced breeders, having acquired abilities increasing the efficiency of their activities [19], may use less energy than inexperienced breeders to breed. Consequently, some of the inexperienced birds would skip reproduction whereas experienced kittiwakes would not in the next season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproductive investment may vary according to factors such as territory quality and age (28)(29)(30), and similarly, the "decision" to skip spawning is likely influenced by internal physiological state. We found that developing females had larger energy reserves than nondeveloping females (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies on natural populations we lack information on individual genotypes, but many studies use the values of these individual components of fitness to infer underlying differences in genotypic fitness and thence to study evolutionary change. These studies have used diverse methods: statistical models of unobserved differences at birth (23)(24)(25); studies of the correlation among fitness components (26)(27)(28); and the use of pedigrees to determine heritability, the fraction of the variance in fitness components that is due to underlying additive genetic variation (1,2,29).…”
mentioning
confidence: 99%